Brushes of semiflexible polymers in equilibrium and under flow in a super-hydrophobic regime - Speyer, Kevin (2015)
We performed molecular dynamics simulations to study the equilibrium and flow properties of a liquid ina nano-channel with confining surfaces coated with a layer of grafted semiflexible polymers. Thecoverage spans a wide range of grafting densities from essentially isolated chains to dense brushes. Theend-grafted polymers were described by a bead spring model with a harmonic potential to includethe bond stiffness of the chains. We varied the rigidity of the chains, from fully flexible polymers to rigidrods, in which the configurational entropy of the chains is negligible. The brush?liquid interaction wastuned to obtain a super-hydrophobic channel, in which the liquid did not penetrate the polymer brush,giving rise to a Cassie?Baxter state. Equilibrium properties such as brush height and bending energywere measured, varying the grafting density and the stiffness of the polymers. We also studied the char-acteristics of the brush?liquid interface and the morphology of the polymer chains supporting the liquidfor different bending rigidities. Non-equilibrium simulations were performed, moving the walls of thechannel in opposite directions at constant speed, obtaining a Couette velocity profile in the bulk liquid.The molecular degrees of freedom of the polymers were studied as a function of the Weissenbergnumber. Also, the violation of the no-slip boundary condition and the slip properties were analyzed as afunction of the shear rate, grafting density and bending stiffness. At high grafting densities, a finite sliplength independent of the shear rate or bending constant was found, while at low grafting densities avery interesting non-monotonic dependence on the bending constant is observed.